2021
DOI: 10.3389/fnagi.2021.702810
|View full text |Cite
|
Sign up to set email alerts
|

Validating Habitual and Goal-Directed Decision-Making Performance Online in Healthy Older Adults

Abstract: Everyday decision-making is supported by a dual-system of control comprised of parallel goal-directed and habitual systems. Over the past decade, the two-stage Markov decision task has become popularized for its ability to dissociate between goal-directed and habitual decision-making. While a handful of studies have implemented decision-making tasks online, only one study has validated the task by comparing in-person and web-based performance on the two-stage task in children and young adults. To date, no stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Our results a priori support the views that aged brains show a higher reliance on antecedent S→R processes and may consequently show enhanced propensity to autonomous behavioural control (Eppinger et al, 2013; Ito et al, 2021; Mata et al, 2010; de Wit et al, 2014). However, such conclusion should be considered carefully—whether propensity to S→ R-like behaviour reflects a core recruitment of a “habit”, model-free, controller as a feature of the aged brain or is simply a consequence of a faulty integration of A→O encoding at any point of learning remains to be answered (Balleine and Dezfouli, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results a priori support the views that aged brains show a higher reliance on antecedent S→R processes and may consequently show enhanced propensity to autonomous behavioural control (Eppinger et al, 2013; Ito et al, 2021; Mata et al, 2010; de Wit et al, 2014). However, such conclusion should be considered carefully—whether propensity to S→ R-like behaviour reflects a core recruitment of a “habit”, model-free, controller as a feature of the aged brain or is simply a consequence of a faulty integration of A→O encoding at any point of learning remains to be answered (Balleine and Dezfouli, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, a second group of factors determining predominance of one or the other process relates to the state of the brain at the moment of learning. Both temporary processes such as sensitisation to drugs (Nelson and Killcross, 2006), working memory loads and stress (Otto et al, 2013), as well as longer-lived states such as drug addiction (Ostlund and Balleine, 2008), stroke (Cognat et al, 2010; Habib, 2004) and ageing (Eppinger et al, 2013; Ito et al, 2021; Mata et al, 2010; de Wit et al, 2014), have been reported to bias goal-directed behavioural command towards an—often detrimental—autonomous control. These conditions share the property of interfering either directly or indirectly with the function of the dorsal striatum, in particular with its medial portion (i.e., the dorsomedial striatum; DMS), an area that is centrally involved in encoding the A→O associative processes supporting goal-directed action (Balleine, 2019).…”
Section: Introductionmentioning
confidence: 99%